The Sustainable Peace Towards Legal Deradicalization Reform - Maskyur Alkhuseri, Muchamad; Hartiwiningsih, Hartiwiningsih; Rustamaji, Muhammad (Lembaga Contrarius Indonesia, 2025)
Indonesia’s national stability and long-term development face serious threats from terrorism and radicalism. Despite introducing anti-terrorism laws and deradicalization programs, efforts mostly rely on repressive strategies. They often fail to address the ideological roots of the problem. This research aims to assess the need for reforming deradicalization policies within a framework of sustainable peace. Such a framework emphasizes the balance between security, social justice, and human rights. Using a juridical-normative and comparative policy approach, the research looks at Indonesia and Malaysia. The findings indicate that Indonesia’s deradicalization efforts are fragmented, lack inter-agency coordination, and lack a comprehensive, multidimensional foundation. In contrast, Malaysia offers a more cohesive model, characterized by institutional synergy and moderate religious education, achieved through partnerships with Islamic authorities. These findings underscore Indonesia’s need for reforms in deradicalization. Such reforms should integrate structural and psychological interventions, enhance institutional accountability, promote cross-sector collaboration, and encourage public engagement. Achieving sustainable peace against evolving radical threats requires human-centered, law-based approaches to promote long-term resilience and inclusivity.